This triangle is a Gandalf triangle: the 45-45-90 one. We can either use the Pythagorean theorem or the formula we derived from it. We should know where the formula comes from, so we'll re-derive it real quick. *a*^{2} + *b*^{2} = *c*^{2}
Since *a* = *b* in our case, we'll replace both with *x*. *x*^{2} + *x*^{2} = 2*a*^{2} = *c*^{2}
Just square root both sides, and presto.
Awesomesauce. Looking at our cut-in-half box, we know the length of one side. That would be *x*, and the hypotenuse is *d*. Multiply and solve.
*c* = 3 × 2 = 6
Done and done. |